Do Arquivo ao Repertório: Passagens pela poesia de Luiz Bacelar - Moura, Fadul (eLyra, 2022)
This research revolves around Frauta de barro (1963), by Luiz Bacellar. It is believed that the Brazilian poet problematizes the limits of “archives” when he works with cultural materials that escape the traditional archiving forms. In order to analyze this issue and the operations within the poems, this paper will take into consideration the notions of archive and repertoire – in consonance with Diana Taylor’s (2013) perspective. In the end, the aim is to bring light to the ways in which the poetry shows its dimensions, erasing limits and disassembling ingrained ideas.